NCAPD2 promotes breast cancer progression through E2F1 transcriptional regulation of CDK1. Issue 3 (25th December 2022) - He, Jinsong; Gao, Rui; Yang, Jianbo; Li, Feng; Fu, Yang; Cui, Junwei; Liu, Xiaoling; Huang, Kanghua; Guo, Qiuyi; Zhou, Zihan; Wei, Wei
Abstract: Breast cancer (BC) is a serious threat to women's health worldwide. Non‐SMC condensin I complex subunit D2 (NCAPD2) is a regulatory subunit of the coagulin I complex, which is mainly involved in chromosome coagulation and separation. The clinical significance, biological behavior, and potential molecular mechanism of NCAPD2 in BC were investigated in this study. We found that NCAPD2 was frequently overexpressed in BC, and it had clinical significance in predicting the prognosis of BC patients. Moreover, loss‐of‐function assays demonstrated that NCAPD2 knockdown restrained the progression of BC by inhibiting proliferation and migration and enhancing apoptosis in vitro. It was further confirmed that the downregulation of NCAPD2 inhibited tumor growth in vivo. NCAPD2 promoted the progression of BC through the extracellular signal–regulated kinase 5 (ERK5) signaling pathway. Additionally, NCAPD2 could transcriptionally activate CDK1 by interacting with E2F transcription factor 1 (E2F1) in MDA‐MB‐231 cells. Overexpression of CDK1 alleviated the inhibitory effects of NCAPD2 knockdown in BC cells. In summary, the NCAPD2/E2F1/CDK1 axis may play a role in promoting the progression of BC, which may provide a blueprint for molecular therapy. Abstract : Non‐SMC condensin I complex subunit D2 (NCAPD2) was frequently overexpressed in breast cancer (BC), and it had clinical significance in predicting the prognosis of BC patients. NCAPD2 knockdown restrained the progression of BC by decreasing proliferation and migration, enhancing apoptosis, and inhibiting tumor growth in mice. NCAPD2 could transcriptionally activate CDK1 by interacting with E2F transcription factor 1 (E2F1) in BC cells.